ANALISIS PERHITUNGAN PAJAK PENGHASILAN PASAL 23 ATAS JASA INSTALASI LISTRIK GUNA MENENTUKAN PAJAK TERUTANG (STUDI KASUS PADA PT WIJAYA KUSUMA SAKTI KEDIRI) - Vera Thessalonica Oktaviyanto; Khasanah Sahara; Ninik Anggraini (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to apply the calculation of Income Tax Article 23 for electrical installation services at PT Wijaya Kusuma Sakti Kediri in order to determine the correct tax payable. Income Tax Article 23 is a tax imposed on income obtained from activities in the service sector carried out by business entities. This research uses quantitative descriptive methods with primary data processed by company staff. The data analysis process involves several stages, starting from determining Taxable Income (PKP) by subtracting net profit before tax from operational expenses, carrying out fiscal reconciliation to ensure conformity between commercial and fiscal financial reports, to calculating the tax payable according to the applicable rates. The results of the research show that the application of Income Tax Article 23 calculations at PT Wijaya Kusuma Sakti Kediri has not yet calculated Income Tax Article 23 in the 2023 period, and there are several obstacles in the timeliness of tax payments and reporting. This research emphasizes the importance of fiscal reconciliation to identify and correct differences between commercial and fiscal financial reports, as well as the importance of compliance with tax regulations to avoid sanctions and fines. Thus, this research makes a significant contribution to understanding the importance of implementing fiscal reconciliation and compliance with tax regulations. These findings can be a guide for other companies in improving the accuracy of tax calculations and minimizing the risk of sanctions from the tax authorities.